Optimization of laser cutting parameter of acrylic by using DMAIC approach - Chua, Yong Ping (2015)
Laser cutting is the most common manufacturing process widely used nowadays and this is due to its flexibility, reliability, maximize material utilization by part nesting, time saving and low cost tooling. But, inappropriate control and setting may lead to material defects, machine malfunction or even catastrophe. Hence, the purpose of this study is to implement the ideas from lean six sigma for optimizing laser cutting conditions to prolong the service life of the laser cutting machine. The entire dissertation will be surrounded in optimize machining parameters for EPILOG Legend 36Ext – Model 9000 laser cutting machine in the FKM lab by using DMAIC approach. And, the whole idea of optimal control was encapsulated in Lean Six Sigma methodology which summarized in the abbreviation (DMAIC): Define, Measure, Analyze, Improve and Control. First of all, a list of problem statement has constructed to clarify the objectives of the project to be studied. Second, a value stream mapping diagram has constructed to serve as an overview of the entire maintenance management system in order to measure the bottlenecks between personnel and information flow from relevant management level. Third, a mathematical modelling software such as MATLAB was used to formulate the relationship between the cutting parameters towards the cutting quality of acrylic specimens. Forth, solutions to machining dysfunctions has proposed and optimum cutting conditions were developed by using Design Expert software. Fifth, a standard practice such as SOP (standard of procedure) was developed to replace current machining procedures. Finally, improved plans were further monitored in order to ensure the improvements were sustainable. After implementing DMAIC, it was found that the information given by supplier’s manual should be continually revised since machining parameters due to deteriorate of machine parts. The values of revising SOP may help FKM lab to save cost in machine repair.